Proyecto de vida y el desarrollo personal, en dos Adolescentes con Discapacidad Intelectual Moderada. (2021)
The present work of degree is proposed as a general objective, to understand how two adolescents diagnosed with moderate intellectual disabilities aged 13 and 16 years, despite the distance and differences in environments, one is located in the rural part of the department of Valle de Cauca and the other in the city of Bogota, are in search of individually develop the life project, reflecting on the different social problems that arise for this population, it is considered of great importance to raise the problem question How do adolescents with moderate intellectual disabilities develop individually the life project?